2007
DOI: 10.1111/j.1745-4530.2007.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Affecting Barrier, Mechanical and Optical Properties of Pectin‐based Films Using Response Surface Methodology

Abstract: Emulsion coatings were formulated and films were developed using pectin as the basic structural component. Preliminary experiments were carried out to determine the proper type and concentration of pectin, lipid and plasticizers in the film. The effects of pectin, beeswax and sorbitol concentration on water vapor permeability (WVP), mechanical properties and opacity of the films were evaluated using the response surface methodology. WVP increased by pectin and sorbitol concentration and was decreased by beeswa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 31 publications
3
22
0
9
Order By: Relevance
“…Turhan and Şahbaz (2004) worked with different methylcellulose concentrations and observed that the higher the concentration, the higher the TS values and the film elongation, referred to concentrations that led to good polysaccharide solubilization and good film-forming solution spreading on the plate. The same tendency was also observed by Maftoonazad, Ramaswamy and Marcotte (2007) for high methoxyl pectin-based films plasticized with sorbitol. In the present research, low polysaccharide concentrations (0.75% and 1%) were used because higher concentrations made it difficult to blend and spread the film-forming solution onto the plate, mainly due to the high viscosity of glucomannan.…”
Section: Polysaccharide and Gelatin Filmssupporting
confidence: 81%
See 1 more Smart Citation
“…Turhan and Şahbaz (2004) worked with different methylcellulose concentrations and observed that the higher the concentration, the higher the TS values and the film elongation, referred to concentrations that led to good polysaccharide solubilization and good film-forming solution spreading on the plate. The same tendency was also observed by Maftoonazad, Ramaswamy and Marcotte (2007) for high methoxyl pectin-based films plasticized with sorbitol. In the present research, low polysaccharide concentrations (0.75% and 1%) were used because higher concentrations made it difficult to blend and spread the film-forming solution onto the plate, mainly due to the high viscosity of glucomannan.…”
Section: Polysaccharide and Gelatin Filmssupporting
confidence: 81%
“…Pectin is a polysaccharide rich in D-galacturonic acid that is mainly obtained from citric peels or apple skin (MAY, 1997) and it may have high or low level of esterification degree; it is also used for films production (MAFTOONAZAD; RAMASWAMY; MARCOTTE, 2007;LIU et al, 2007).…”
Section: Film Formationmentioning
confidence: 99%
“…La incorporación de lípidos supone pérdidas de brillo por la aparición de partículas grasas en la superficie, resultado de los procesos de floculación, coalescencia y cremado de los glóbulos grasos durante el secado de la película (Trezza y Krochta, 2000;Villalobos et al, 2005, Maftoonazad et al, 2007a. La apariencia (brillo, transparencia, color, opacidad) depende de la naturaleza del componente formador de la matriz del film, pero está muy afectada por la presencia de componentes no miscibles que sufren los procesos de desestabilización mencionados durante la formación del la película.…”
Section: Componentes Y Métodos De Obtención De Films Y Recubrimientosunclassified
“…El área bajo la curva se define como la opacidad de la muestra en nm (Maftoonazad, et al, 2007a). Este parámetro puede dar indicios indirectos de la estructura del film: estructuras rugosas, generalmente son más opacas.…”
Section: (I4)unclassified
See 1 more Smart Citation